An analysis of the effect of management participation in director selection on the long-term performance of the firm - Callahan, William T; Millar, James A; Schulman, Craig (Journal of Corporate Finance, 2003)
A major criticism of corporate boards of directors is the absence of objectivity in appraising and monitoring management [The Business Lawyer, 48 (1992) 59–77]. Recently, Shivdasani and Yermack [Journal of Finance LIV (5) (1999) 1829] find that CEO involvement in board selection is associated with a greater proportion of gray and a lower proportion of outside director appointments. The question addressed here is whether corporate performance, as measured by Tobin's q, is affected by management influence in the board nominating process. Agrawal and Knoeber [Journal of Financial and Quantitative Analysis, 31 (3) (1996) 377] find interdependence among seven mechanisms to control agency problems between managers and stockholders. Their finding suggests that cross-sectional OLS regressions of firm performance on a single mechanism may be misleading and that interpretation of multiple regression methods is weakened by multicollinearity. In this study, a principal component analysis (PCA) is employed to mitigate such problems. An index of management involvement in director nomination is constructed for a sample of 106 firms from 1989 to 1992 via a PCA method utilizing selected governance mechanisms within the nominating process. We find a positive relationship between management participation in the director selection process and corporate performance.